Food, vigilance, and sperm: the role of male direct benefits in the evolution of female preference in a polygamous bird - Pizzari, T (2003)
The adaptive significance of female selection of copulation partners remains unresolved, particularly in polygamous species where males do not provide paternal care. In these species the possibility that direct benefits other than paternal care may play an important role in the evolution of female choice has received little attention. I tested whether direct benefits are associated with female choice in the polygamous feral fowl, Gallus g. domesticus, where females prefer socially dominant copulation partners and males do not care for the young but do provide females with three commodities: food, vigilance, and sperm. I used a combination of empirical and experimental data to show that male propensity to offer food and vigilance, but not sperm, was positively associated with male social status, suggesting that the provision of these resources may be costly and condition dependent in males. Copulation success was correlated with male status but not with the number of feedings a female received from a male, indicating that a female preferred dominant partners that in general provided any female with more food, rather than partners that provided only her with more food, consistent with the idea that females may use male resource provisioning as a proximate mechanism to assess male condition. Together, these results indicate that male resources provisioning is (1) tightly linked to male social status, (2) a potential indicator of male condition and possibly genetic quality, and (3) a potential criterion for females to select dominant partners, thus playing an important role in the evolution of partner choice even in polygamous species lacking paternal care.